A place with a view: A first‐person perspective in the hippocampal memory space. Issue 5 (3rd April 2023) - Wirth, Sylvia
Abstract: How do rodents' and primates' differences in visual perception impact the way the brain constructs egocentric and allocentric reference frames to represent stimuli in space? Strikingly, there are important similarities in the egocentric spatial reference frames through which cortical regions represent objects with respect to an animal's head or body in rodents and primates. These egocentric representations are suitable for navigation across species. However, while the rodent hippocampus represents allocentric place, I draw on several pieces of evidence suggesting that an egocentric reference frame is paramount in the primate hippocampus, and relates to the first‐person perspective characteristic of a primate's field of view. I further discuss the link between an allocentric reference frame and a conceptual frame to suggest that an allocentric reference frame is a semantic construct in primates. Finally, I discuss how views probe memory recall and support prospective coding, and as they are based on a first‐person perspective, are a powerful tool for probing episodic memory across species.